NLP in a post-truth world. (31st January 2017) - DALE, ROBERT
Abstract: We live in a post-truth world. It now matters more whether people think something is true than whether something really is true. This is dangerous, and technology is at least partly to blame. So, as technologists, how can we help to fix this?